Problematizing Foucauldian Ethics: A Review of Technologies of the Self in Sociology of Sport Since 2003. (February 2017) - Crocket, Hamish
Foucault's technologies of the self have been used by sociological scholars of sport for nearly two decades. Yet Markula's seminal articulation of a feminist Foucauldian ethics in 2003 stands as a watershed publication, insofar as the majority of publications following this article have framed much of their analyses in relation to this work. In this article, then, I review sociological studies of sport and exercise that draw on Foucauldian ethics from Markula's article onward, paying careful attention to how Foucault's ethics and Markula's Foucauldian feminism have been deployed. Although I interpret this body of work as productive and insightful, I offer a critical reading of the emphasis on explicit problematizations and, relatedly, develop a methodological critique of researchers' reliance on interviews as a prime form of research method.